Diverse roles of mtDNA in schizophrenia: Implications in its pathophysiology and as biomarker for cognitive impairment. (September 2020) - Suárez-Méndez, Samuel; García-de la Cruz, Dulce Dajheanne; Tovilla-Zárate, Carlos Alfonso; Genis-Mendoza, Alma Delia; Ramón-Torres, Rosa Angélica; González-Castro, Thelma Beatriz; Juárez-Rojop, Isela Esther
Abstract: Schizophrenia (SZ) is a mental disorder characterized by neurocognitive dysfunctions and a reduction in occupational and social functioning. Several studies have provided evidence for mitochondrial dysfunction in the pathophysiology of SZ. In this sense, it is known that the addition of genetic variations in mitochondrial DNA (mtDNA) impairs oxidative phosphorylation of enzymatic complexes in mitochondria, resulting in ATP depletion and subsequent enhancement of reactive oxygen species; this is associated with cellular degeneration and apoptosis observed in some neuropsychiatric disorders. As a consequence of mitochondrial dysfunction, an increase in circulating cell-free mtDNA fragments can occur, which has been observed in individuals with SZ. Moreover, due to the bacterial origin of mitochondria, these cell-free mtDNA fragments in blood plasma may induce inflammatory and immunogenic responses, especially when their release is enhanced in specific disease conditions. However, the exact mechanism by which mtDNA could be released into blood plasma is not yet clear. Therefore, the aims of this review article were to discuss the participation of mtDNA genetic variations in physiopathologic mechanisms of SZ, and to determine the status of the disease and the possible ensuing changes over time by using circulating cell-free mtDNA fragments as a biomarker.